Effects of micro particle reinforcement on mechanical properties of 3D printed parts. Issue 1 (2nd January 2018) - Çantı, Ebubekir; Aydın, Mustafa
Abstract : Purpose: The purpose of this paper is to characterize the effects of different micro particle reinforcement with same weight ratio in acrylonitrile-butadiene-styrene (ABS) feed-stocks for 3D printing process. Design/methodology/approach: In this study, composite filaments were produced by using a co-rotational twin screw extruder and used as building material to print samples in a commercial fused deposition modeling (FDM) 3D printer. The reinforcement particles, ZrB2 and Al, have different properties, including density, surface area, purity and particle morphology, and were expected to improve mechanical properties of 3D printed samples. Differential calorimetry scanning and melt flow index studies were applied on the materials to observe the change in glass transition temperatures and melt flow behaviors, respectively. Also, to evaluate the mechanical properties, tensile and three-point bending test were carried out. Fractured surfaces were characterized via energy-dispersive X-ray spectroscopy for validation of the reinforcements in the ABS matrix. Moreover, scanning electron microscope micrograph examination was conducted on the fractured surfaces to characterize fracture modes. Findings: For 3D printed samples, a strain increase of at least 82.5 per cent was achieved by using micro particle reinforcement with a weight ratio of 1.5 per cent. Research limitations/implications: Higher filler ratios of the reinforcement particles cause loss on the printability of the feed-stocks. Practical implications: Reinforced ABS stands out as a possible solution to overcome robustness problems in FDM printing. Originality/value: Even though the effects of printing parameters on the mechanical properties of 3D printed parts have been vastly studied in the literature, studies conducted on improvement of the building materials are limited. This paper proposes to create novel feed-stock materials for achieving printed parts with superior properties using polymer composites.